Get into pharmacy school : Rx for success! - Figg, William Douglas; Chau, Cindy H. (New York : Kaplan Publishing, 2011)
This guidebook will introduce you to the profession, provide detailed guidance on how to apply to pharmacy school, give you glimpse of what to expect while you're in school, and point out in the direction of the various pathways you can take as a pharmacists.
Is pharmacy school for you? -- Planning for pharmacy school -- Applying to pharmacy school- navigating the application -- Preparing for your career in pharmacy -- Financing your degree -- Resources
Includes bibliography and index.
Keywords: CAREER CHOICE; PHARMACY VOCATIONAL GUIDANCE